An Investigation Into the Determinants of Savings and Investment - Adriel Analyn (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study investigated the correlation between savings, investment, and economic growth. An implication of this research is the identification of the input of production that has a greater impact on economic growth. The study used an ARDL model to analyze time series data collected over a period of twenty years. The findings indicate a direct correlation between savings, investment, and economic growth. The study's most notable finding is the confirmation of labor's significant influence on economic growth, surpassing the contribution of capital.